1983
DOI: 10.1007/bf00043357
|View full text |Cite
|
Sign up to set email alerts
|

Picloram induced somatic embryogenesis in Gasteria and Haworthia

Abstract: Various leaf sections of Gasteria verrucosa Haw. and Haworthia fasciata Haw. were cultured on media to examine the effect of picloram (4-amino 3, 5, 6-trichloropicolinic acid) and 2, 4-D (2, 4-dichlorophenoxy acetic acid) on somatic embryogenesis. Picloram (0.5, 1.0, 2.0, 3.0mg1-1 ) outperformed 2,4-D (0, 1.0, 2.0, 3.0mg1-1 ) as the auxin source of both earliness of callus and embryo induction and final yield of embryos produced at both kinetin levels examined (0.25, 1.0mgl -~ ). Embryos arose initially as a y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
2

Year Published

1984
1984
2013
2013

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 10 publications
2
15
2
Order By: Relevance
“…In Agapanthus africanus, however, somatic embryogenesis was not induced by 2, 4-D but by picloram. The effectiveness of picloram for inducing somatic embryogenesis has also been reported in some other monocotyledonous plants [10,11] as well as some dicots such as pea [12] and chickpea [13]. Because of the high ability in regeneration and multiplication, the plant regeneration systems of agapanthus established in the present study will be efficiently used for rapid clonal propagation if the micropropagated plants have no aberrant somaclonal variations.…”
Section: Discussionsupporting
confidence: 67%
“…In Agapanthus africanus, however, somatic embryogenesis was not induced by 2, 4-D but by picloram. The effectiveness of picloram for inducing somatic embryogenesis has also been reported in some other monocotyledonous plants [10,11] as well as some dicots such as pea [12] and chickpea [13]. Because of the high ability in regeneration and multiplication, the plant regeneration systems of agapanthus established in the present study will be efficiently used for rapid clonal propagation if the micropropagated plants have no aberrant somaclonal variations.…”
Section: Discussionsupporting
confidence: 67%
“…In contrast to previous experiments, where somatic embryogenesis was attempted by transfer of pea cells or callus to hormone-free media (Jacobsen, unpublished results), the transfer of callus tissues to liquid media with low picloram concentration was successful, thus confirming the suggestions of others [2,5] that lower concentrations of picloram might be advantageous. Although the embryos in the present study were not derived from free single cells or micro clusters but from embryoids formed at the surface of callus tissues, their occurrence proves the general ability of pea, and possibly other seed legumes, to form somatic embryos.…”
Section: Resultscontrasting
confidence: 50%
“…It has already been reported that picloram gave better results than 2,4-D for both callus induction and subsequent morphogenesis in several Liliaceous species: somatic embryogenesis from leaf sections of Gasteria and Haworthia (Beyl and Sharma, 1983), and callus formation and plant regeneration from shoot tips of Allium cepa (Phillips and Luteyn, 1983). The present study showed for the first time that picloram had beneficial effects on haploid induction in anther cultures of Lilium species.…”
Section: Discussionmentioning
confidence: 95%